2010
DOI: 10.1111/j.1553-2712.2010.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Inaccuracy of the Global Assessment Score in the Emergency Medicine Standard Letter of Recommendation

Abstract: Standard letter of recommendation writers are inaccurate in estimating the ROL position of the applicant using the GAS tier criteria. The GAS tiers were accurate only 26% of the time. Because of the valuable role that the SLOR plays in determining an applicant's competitiveness in the National Resident Matching Program (NRMP) in EM, future discussion should focus on improving the consistency and accuracy of the GAS section. Furthermore, there needs to be a national dialogue to reassess the utility of the crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…The use of SLORs may represent a more efficient and dependable replacement for this less reliable tool for candidate assessment in pediatric otolaryngology fellowship selection. The SLOR created by the Council of Emergency Medicine Residency Directors has proven to be an effective means of curtailing the variety of information presented in an NLOR for residency applicants,8, 9 despite the fact that a recent report demonstrated that the global assessment score is only accurate 26% of the time 24. The higher mean and median rankings of the SLOR for writer background, applicant comparison to contemporaries, and applicant qualifications for pediatric otolaryngology in the SLOR may be indicative of the fact that some of the NLORs did not include this information.…”
Section: Discussionmentioning
confidence: 99%
“…The use of SLORs may represent a more efficient and dependable replacement for this less reliable tool for candidate assessment in pediatric otolaryngology fellowship selection. The SLOR created by the Council of Emergency Medicine Residency Directors has proven to be an effective means of curtailing the variety of information presented in an NLOR for residency applicants,8, 9 despite the fact that a recent report demonstrated that the global assessment score is only accurate 26% of the time 24. The higher mean and median rankings of the SLOR for writer background, applicant comparison to contemporaries, and applicant qualifications for pediatric otolaryngology in the SLOR may be indicative of the fact that some of the NLORs did not include this information.…”
Section: Discussionmentioning
confidence: 99%
“…Applicants are evaluated by residency programs based on various components of their application including United States Medical Licensing Examination (USMLE) scores, the dean’s performance evaluation, clinical rotation grades, extracurricular experiences, the medical school’s reputation, and letters of recommendation 14…”
Section: Introductionmentioning
confidence: 99%
“…7 While there are many benefits of the SLOE, 1,3,9,10 it is unclear whether the SLOE can predict future performance. [11][12][13] The SLOE ranks students in various aspects of their EM clerkship performance (e.g., work ethic, team work, anticipated level of guidance needed). 9 The global assessment section (section C) of the SLOE places the student into a quantile for two questions.…”
mentioning
confidence: 99%